Somatic-vegetative Symptoms Evolution in Postmenopausal Women Treated with Phytoestrogens and Hormone Replacement Therapy - Delia Mirela ŢIŢ; Annamaria PALLAG; Ciprian IOVAN; Gheorghe FURĂU; Cristian FURĂU; Simona BUNGĂU (Tehran University of Medical Sciences, 2017)
Background: The purpose of this study was to compare the effects of the phytoestrogens in relieving and/or suppressing the specific somatic-vegetative symptoms of menopause with those of the hormone therapy, administered in small doses. Methods: The study was conducted in the County Clinical Emergency Hospital Oradea - Obstetric-Gynecological Ambulatory, and in private obstetrics-gynecology cabinets from Bihor County (NW Romania), from November 2011 to January 2014. Overall, 325 patients clinically diagnosed with specific postmenopausal symptomatology and not previously treated with phytoestrogens or hormone replacement therapy (HRT), were divided into 3 groups. Symptom assessment was performed with a standardized questionnaire named Menopause Rating Scale (MRS) in three phases: beginning of the treatment, after six months, and after one year. The administered doses for three different groups were as follows: 1 mg estradiol and 0.5 mg norethisterone acetate (NETA) p.o. daily (i.e. for the HRT group); 40 mg of isoflavones p.o. daily - i.e. 2 capsules of 40% standardized extract containing 20 mg of pure isoflavones: Genistein, Daidzein, and Glycitein (i.e. for the group with phytoestrogens); and no trreatment for the control group. Results: The evolution of the somatic-vegetative symptoms was better in both groups treated either with phytoestrogens or HRT (P<0.001) as opposed to the higher percentage of patients with stationary symptoms in the control group (i.e. 37.74% for control group, 16.13% for the group treated with phytoestrogens, respectively 18.95% for the group treated with HRT). Conclusion: Twelve months treatment study is a favorable evidence for the use of soy derived phytoestrogens in the treatment of somatic-vegetative symptoms at postmenopausal women.